2002
DOI: 10.1074/jbc.m110608200
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of Differentiated Phenotype of Articular Chondrocytes by Protein Kinase C and Extracellular Signal-regulated Protein Kinase

Abstract: The differentiated phenotype of chondrocyte is rapidly lost during in vitro culture by a process designated "dedifferentiation." In this study, we investigate the roles of protein kinase C (PKC) and extracellular signalregulated protein kinase (ERK) in the maintenance of the differentiated chondrocyte phenotype. Chondrocytes isolated from rabbit articular cartilage underwent dedifferentiation upon serial monolayer culture with cessation of type II collagen expression and proteoglycan synthesis, which was rever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
166
1
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 153 publications
(178 citation statements)
references
References 40 publications
9
166
1
2
Order By: Relevance
“…Our current finding is intriguing in that ␣v␤5 integrin plays a pivotal role in the dedifferentiation of chondrocytes through the activation of ERK signaling. Although the involvement of ERK signaling in dedifferentiation has been reported (47,48), our finding is novel in that we demonstrated that the ERK signaling is activated by ␣v␤5 integrin.…”
Section: Discussionsupporting
confidence: 51%
“…Our current finding is intriguing in that ␣v␤5 integrin plays a pivotal role in the dedifferentiation of chondrocytes through the activation of ERK signaling. Although the involvement of ERK signaling in dedifferentiation has been reported (47,48), our finding is novel in that we demonstrated that the ERK signaling is activated by ␣v␤5 integrin.…”
Section: Discussionsupporting
confidence: 51%
“…32 Briefly, cartilage slices were dissociated enzymatically for 6 h in 0.2% collagenase type II (381 U/mg solid, Sigma, St. Louis, MO, USA) in Dulbecco's modified Eagle's medium (DMEM) (Gibco-BRL, Rockville, MD, USA). The cells were plated on culture dishes at a density of 5 Â 10 4 cells/cm 2 in DMEM containing 10% bovine serum.…”
Section: Cell Culturementioning
confidence: 99%
“…Rabbit articular chondrocytes were isolated from knee joint cartilage slices of 2-week-old New Zealand white rabbits as described by Yoon et al (2002) (7). Briefly, cartilage slices were dissociated for 6 h in 0.2% collagenase type II in prolinefree Dulbecco's modified Eagle's medium (DMEM; Gibco-BRL, Gaithersburg, MD).…”
Section: Primary Culture Of Rabbit Articular Chondrocytesmentioning
confidence: 99%
“…For instance, both down-regulation of ERK1/2 and induction of p38 kinase activities are required for chondrogenic differentiation of mesenchymal cells (10,11), and activation of ERK1/2 in differentiated articular chondrocytes causes dedifferentiation (7). ERK1/2 and p38 kinase also oppositely regulate NOinduced dedifferentiation and apoptosis of chondrocytes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation